Examining the Impact of Behavioral Bias of Mental Accounting by Investors on Financial Policies of Companies Listed on the Tehran Stock Exchange - Shahsavari , Mohamad Sadegh; Ranjbar, Mohammad Hossein; Salari , Hojjatallah; Amiri , Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study investigates the impact of the behavioral bias of mental accounting by investors on the financial policies of companies listed on the Tehran Stock Exchange. Methodology: The statistical population of the study comprises 14 leading investment companies and their investee companies, totaling 109 companies, during the period 2014–2020. Financial leverage, dividend payouts, and the debt ratio were used as indicators of financial policy. Data analysis was conducted using panel data models and STATA software. Findings: The results indicated that the analyzed investment companies exhibited the behavioral bias of mental accounting in 35.71% of cases. Furthermore, mental accounting by investors had a significant inverse impact on financial leverage, a negative impact on homogeneous cash dividends, and a significant direct impact on the debt ratio as financial policy indicators of the companies. Conclusion: The study confirms that mental accounting influences financial policies by altering financing behaviors, especially regarding debt maturity and long-term debt-to-equity ratio. However, its effect on the relationship between growth opportunities and tangible fixed asset growth is negligible. These findings align indirectly with theoretical and empirical literature, such as prospect theory and disposition effect studies, indicating a broader behavioral bias in investment and financing decisions. The study highlights the need for further research to explore mental accounting’s broader implications in financial and investment policy-making.